13th W&J National Painting Show. - the Commons Gallery, Washington (Washington : Washington & Jefferson College, 1981)
Ajami, Joselyn ; Andrus, Damian ; Bailey, Elizabeth ; Bauhs, Kathleen Gorman ; Beckerman, Nancy ; Bissell, Ann Angel ; Boston, Joyce ; Carfagno, M. ; Cohen, Jill ; Dearing, Shirley ; Dienstbier, Karen ; Dorsey, Michael A. ; etc.
13th W&J National Painting Show, the Commons Gallery, Washington, April 5-25, 1981
Engels
kunstcatalogus